1998
DOI: 10.1002/(sici)1099-1417(199807/08)13:4<293::aid-jqs370>3.0.co;2-s
|View full text |Cite
|
Sign up to set email alerts
|

Rock glaciers on the Faeroe Islands, the North Atlantic

Abstract: Three sites with alleged relict rock glaciers are described from southern Faeroe Islands, in the North Atlantic Ocean. The rock glaciers represent both talus‐derived and glacier‐derived types and were most likely initiated during the late Weichselian. One of the rock glaciers apparently became unstable at some point during degradation of permafrost and was subsequently transformed by a landslide. The age of the rock glaciers are not known precisely, but a Younger Dryas age is suggested, partly by considering c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
22
0

Year Published

1998
1998
2011
2011

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 67 publications
(90 reference statements)
0
22
0
Order By: Relevance
“…Kerschner, 1978;De Jong and Kwadjik, 1988) but also in mountainous areas where permafrost and active rock glaciers no longer exist (e.g. Jeanneret, 1975;Humlum, 1998b;Hughes et al, 2003). Relict rock glaciers usually retain some of the morphological hallmarks of their active counterparts, notably well-defined margins, lateral and terminal ridges, nested inner transverse ridges, enclosed depressions, and a surface mantle of coarse angular debris (Fig.…”
Section: Introductionmentioning
confidence: 92%
“…Kerschner, 1978;De Jong and Kwadjik, 1988) but also in mountainous areas where permafrost and active rock glaciers no longer exist (e.g. Jeanneret, 1975;Humlum, 1998b;Hughes et al, 2003). Relict rock glaciers usually retain some of the morphological hallmarks of their active counterparts, notably well-defined margins, lateral and terminal ridges, nested inner transverse ridges, enclosed depressions, and a surface mantle of coarse angular debris (Fig.…”
Section: Introductionmentioning
confidence: 92%
“…These effects mean that the density of surface waters is increased, and surface NAC waters sink to form North Atlantic deep water (NADW), which then flows southwards at depth. The formation of NADW releases a large amount of latent heat that plays a major role in regulation of both North Atlantic and global climates (Broecker et al, 1985;Lehman and Keigwin, 1992;Humlum, 1998) Arctic-dominated waters of the EGC (Hjort et al, 1973). This results in a gradient of apparent surface-water ages across the interface between Atlantic and Arctic water known as the Polar Front that reflects climatic and oceanographic gradients (Eiríksson et al, 2004).…”
Section: Figurementioning
confidence: 99%
“…Significant shifts in oceanographic and climatic variables have been identified within both the wider North Atlantic and the study area during the Holocene, including the location and intensity of surface and deep-water currents. During colder phases, features such as increased sea-ice cover may surround areas including the Faroes as a body of cold polar waters extends from Figure 2 the East Iceland Current towards the Faroes from the north (Moros et al, 1997;Humlum, 1998;Kuijpers et al, 1998;. Variability in the relative influence of Atlantic and Arctic waters around Iceland has also been identified over short timescales (Knudsen et al, 2004), and a relationship has been identified between variability in the influence of Arctic and Atlantic water masses and MRE values on the North Iceland shelf over the past c.4000 years Larsen et al, 2002;Eiríksson et al, 2004).…”
mentioning
confidence: 99%
“…Many are several thousand years old (e.g. Kaeaeb et al 1997;Calkin et al 1998) and some relict rock glaciers are believed to have formed at the end of the last Ice Age about 10 ka ago (Sandeman & Ballantyne 1996;Humlum 1998). The occurrence of past or present glaciers is not a necessary prelude to the formation of rock glaciers because these landforms exist in both glacial and non-glacial areas.…”
mentioning
confidence: 99%